2020
DOI: 10.1108/ijchm-01-2020-0001
|View full text |Cite
|
Sign up to set email alerts
|

Tolerating errors in hospitality organizations: relationships with learning behavior, error reporting and service recovery performance

Abstract: Purpose Hospitality work setting is error-prone, rendering error handling critical for effective organizational operation and quality of service delivery. An organization’s attitude toward errors can be traced back to one fundamental question: should errors be tolerated/accepted or not? This study aims to examine the relationships between error tolerance and hospitality employees’ three critical work behaviors, namely, learning beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 103 publications
0
39
0
3
Order By: Relevance
“…Many positive examples of learning from mistakes have emerged from entrepreneurship studies, that is, from entrepreneurial learnings from business failures (Cardon et al, 2011;Cope, 2011;Eggers and Song, 2015;McGrath, 1999;Politis and Gabrielsson, 2009;Shepherd, 2003;Yamakawa and Cardon, 2015). Recent studies on the hospitality industry (Guchait et al, 2016(Guchait et al, , 2018Pasamehmetoglu et al, 2017;Jung and Yoon, 2017;Wang et al, 2020) simplified the organizational attitude toward errors to the primary question: Should mistakes at work be tolerated? As they observed that error tolerance yields positive outcomes for employees, such as psychological safety, self-efficacy, supportive employee behaviors, employee learning and increased error reporting ratesthey asserted that it should be tolerated.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Many positive examples of learning from mistakes have emerged from entrepreneurship studies, that is, from entrepreneurial learnings from business failures (Cardon et al, 2011;Cope, 2011;Eggers and Song, 2015;McGrath, 1999;Politis and Gabrielsson, 2009;Shepherd, 2003;Yamakawa and Cardon, 2015). Recent studies on the hospitality industry (Guchait et al, 2016(Guchait et al, , 2018Pasamehmetoglu et al, 2017;Jung and Yoon, 2017;Wang et al, 2020) simplified the organizational attitude toward errors to the primary question: Should mistakes at work be tolerated? As they observed that error tolerance yields positive outcomes for employees, such as psychological safety, self-efficacy, supportive employee behaviors, employee learning and increased error reporting ratesthey asserted that it should be tolerated.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Managers can determine how the collected information can be used. For example, sharing customers' compliments in a shift meeting can acknowledge the corresponding employees' performance well and facilitate an uplifting experience for the whole team as service production entails close collaborations among team members (Wang et al, 2020).…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Second, hospitality service often results from sequential and concerted efforts among employees in different departments. Therefore, teamwork is crucial for successful service delivery (Wang et al, 2020). Converging evidence demonstrates that helping behavior is positively associated with service quality (Yoon and Suh, 2003), organizational effectiveness (MacKenzie et al, 2011) and customer satisfaction (Walz and Niehoff, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Content resources, interaction patterns, collaborative models, organizational planning and influencing factors related to learning processes constitute learning behaviors, which are also key elements to describe learning behaviors [1,2]. The learning processes supported by online technology and data technology ensure the completeness and continuity of learning behavior data.…”
Section: Introductionmentioning
confidence: 99%